Tuar Mhic Eadaigh : stair agus seanchas - Standún, Pádraig, 1946- (Clo Iar-Chonnachta Teo, 2010)
A social history of the village of Tourmakeady, Co. Mayo, recounted here by novelist Padraig Standun who has been curate in the village since 1995.